Verbal and Visual Signs of Advertisement in National Geographic Traveller Magazine - Okta Prawiranatha, I Gede Putu (Humanis; Vol 22 No 4 (2018)DO - 10.24843/JH.2018.v22.i04.p26, 2018)
This article is entitled “Verbal and Visual Signs of Advertisement in National Geographic Traveller Magazine” .  The aims are to describe the meaning and function of verbal and visual signs and how their interrelations are. The source of the National Geographic Traveller Magazine from which the three advertisements are selected, these selections are due to advertisements present good combination of colors, pictures and word choices than another advertisement which also consist of verbal and visual signs. The research is done through library research with documentation method and observation technique was applied to collect the data, the qualitative method was used to analyze the data based on the theory of meaning and function by Leech, theory of signs by Chandler, and use of color by Cerrato. The result of the analysis shows that the advertiser tends to use conceptual meaning and informational function to deliver or give information to the readers about the product itself. The verbal and visual signs are related to one another, verbal sign as the part that describes what is meant by visual sign and the visual sign as the part that illustrates what is meant by the verbal sign. So, what is shown in the visual sign is appropriate with what is written in the verbal sign and vice versa.